Molecular Determinants of Human T-cell Leukemia Virus Type 1 Gag Targeting to the Plasma Membrane for Assembly. Issue 12 (30th June 2022) - Herrmann, Dominik; Hanson, Heather M.; Zhou, Lynne W.; Addabbo, Rayna; Willkomm, Nora A.; Angert, Isaac; Mueller, Joachim D.; Mansky, Louis M.; Saad, Jamil S.
Graphical abstract: Highlights: Molecular determinants of HTLV-1 MA–plasma membrane defined. PI(4, 5)P2 binding to the lysine-rich motif is essential for VLP production. PS binds to the unstructured N-terminal arginine-rich motif. PI(4, 5)P2 binding to MA is enhanced by the arginine-rich motif. Distinct lipid binding motifs mediate HTLV-1 Gag binding to PM and VLP production. Abstract: Assembly of human T-cell leukemia virus type 1 (HTLV-1) particles is initiated by the trafficking of virally encoded Gag polyproteins to the inner leaflet of the plasma membrane (PM). Gag–PM interactions are mediated by the matrix (MA) domain, which contains a myristoyl group (myr) and a basic patch formed by lysine and arginine residues. For many retroviruses, Gag–PM interactions are mediated by phosphatidylinositol 4, 5-bisphosphate [PI(4, 5)P2 ]; however, previous studies suggested that HTLV-1 Gag–PM interactions and therefore virus assembly are less dependent on PI(4, 5)P2 . We have recently shown that PI(4, 5)P2 binds directly to HTLV-1 unmyristoylated MA [myr(–)MA] and that myr(–)MA binding to membranes is significantly enhanced by inclusion of phosphatidylserine (PS) and PI(4, 5)P2 . Herein, we employed structural, biophysical, biochemical, mutagenesis, and cell-based assays to identify residues involved in MA–membrane interactions. Our data revealed that the lysine-rich motif (Lys47, Lys48, and Lys51) constitutes the primary PI(4, 5)P2 –binding site. Furthermore, we show that arginine residues 3, 7, 14 and 17 located in the unstructured N-terminus are essential for MA binding to membranes containing PS and/or PI(4, 5)P2 . Substitution of lysine and arginine residues severely attenuated virus-like particle production, but only the lysine residues could be clearly correlated with reduced PM binding. These results support a mechanism by which HTLV-1 Gag targeting to the PM is mediated by a trio engagement of the myr group, Arg-rich and Lys-rich motifs. These findings advance our understanding of a key step in retroviral particle assembly.